2006
DOI: 10.1161/circulationaha.105.594531
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Chamber Versus Single-Chamber Detection Enhancements for Implantable Defibrillator Rhythm Diagnosis

Abstract: Background-Delivery of inappropriate shocks caused by misdetection of supraventricular tachycardia (SVT) remains a substantial complication of implanted cardioverter/defibrillator (ICD) therapy. Whether use of optimally programmed dual-chamber ICDs lowers this risk compared with that in single-chamber ICDs is not clear. Methods and Results-Subjects with a clinical indication for ICD (nϭ400) at 27 participating centers received dual-chamber ICDs and were randomly assigned to strictly defined optimal single-or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
139
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(145 citation statements)
references
References 25 publications
3
139
2
1
Order By: Relevance
“…Clinical trials and simulated testing of induced arrhythmias that compared single-vs dual-chamber discriminators have reported inconsistent results [10,33,[137][138][139]. Two meta-analyses found no superiority of dual-chamber ICDs in terms of mortality or inappropriate therapies [11,140].…”
Section: Dual-chamber Vs Single-chamber Algorithmsmentioning
confidence: 99%
“…Clinical trials and simulated testing of induced arrhythmias that compared single-vs dual-chamber discriminators have reported inconsistent results [10,33,[137][138][139]. Two meta-analyses found no superiority of dual-chamber ICDs in terms of mortality or inappropriate therapies [11,140].…”
Section: Dual-chamber Vs Single-chamber Algorithmsmentioning
confidence: 99%
“…Some reports suggested that the dual-chamber ICD provided clinical benefits in arrhythmia differentiation, prevention of inappropriate ICD therapy and patients who required pacing for bradyarrhythmias. (25)(26)(27)(28)(29) However, Dewland et al pointed out that complications were more frequent during the implantation of dual-versus single-chamber ICDs (3.17% vs. 2.11%; p < 0.001), with a higher in-hospital mortality (0.40% vs. 0.23%; p < 0.001). (24) Taking into account existing best evidence, American and European guidelines (19,30) …”
Section: Implantable Cardioverter Defibrillatormentioning
confidence: 99%
“…19,20) Several studies have reported that dual chamber ICD decrease inappropriate therapies. 21,22) Because the dual chamber ICD can record atrial and ventricular intracardiac electrograms, a dual chamber ICD can diagnose tachy-arrhythmias more accurately than a single chamber ICD. In the present study, the actual percentage of inappropriate therapy was smaller in dual chamber ICD than single chamber ICD, but this point of "dual/ single chamber" was not an independent predictor in our evaluation.…”
Section: Predictors Of Inappropriate Therapy During the Initial Obsermentioning
confidence: 99%